2009
DOI: 10.1073/pnas.0910981106
|View full text |Cite
|
Sign up to set email alerts
|

World Color Survey color naming reveals universal motifs and their within-language diversity

Abstract: We analyzed the color terms in the World Color Survey (WCS) (www.icsi.berkeley.edu/wcs/), a large color-naming database obtained from informants of mostly unwritten languages spoken in preindustrialized cultures that have had limited contact with modern, industrialized society. The color naming idiolects of 2,367 WCS informants fall into three to six ''motifs,'' where each motif is a different color-naming system based on a subset of a universal glossary of 11 color terms. These motifs are universal in that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 20 publications
8
90
0
Order By: Relevance
“…We show correspondence between infant and lexical color categories for a selection of three WCS languages, yet inspection of naming data from the other WCS languages reveals correspondences for many other languages as well. We also find that infants' categorical distinctions align with three of the categorical distinctions in the GBPm (12). Fig.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…We show correspondence between infant and lexical color categories for a selection of three WCS languages, yet inspection of naming data from the other WCS languages reveals correspondences for many other languages as well. We also find that infants' categorical distinctions align with three of the categorical distinctions in the GBPm (12). Fig.…”
Section: Resultssupporting
confidence: 50%
“…The gaps align qualitatively well with the low points in the bar plot, corresponding to few WCS centroids. Distinctions (42); and the GBPm for row G stimuli (12). Vertical thick black lines indicate category boundaries between stimuli given the same most frequent term within a language.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study that applied cluster analysis (39) to the data of the World Color Survey (www1.ICSI.Berkeley.EDU/wcs/), a corpus of color-naming data from 110 unwritten languages, revealed that the particular structure of color terms used by each language is drawn on a set of about three to six universal color-naming systems. Notably, the results of that study suggested that the pattern of categorization for colors between blue and green could be classified into about four types of "motifs" that are common across various mother languages, original habitations, and cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest difference Jäger found between his PCA analysis and the non-statistical analysis of Kay & Maffi (1999) was that he found yellow more frequently associated with white than they did (p. 533). In a follow-up analysis to their 2006 paper, Lindsey and Brown (2009) found that although there is significant variation across speakers of the same language,…”
mentioning
confidence: 99%